1975
DOI: 10.1111/j.1476-5381.1975.tb06927.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Inhibitory Receptor in Rat Hippocampus: A Microiontophoretic Study Using Con‐formationally Restricted Amino Acid Analogues

Abstract: I Pyramidal cells in rat hippocampus were used to study the molecular dimensions of a receptor for inhibitory amino acids in the central nervous system. The inhibitory potencies of y-aminobutyrate (GABA), ,B-alanine and glycine were compared by standard microiontophoretic techniques. Subsequently, rigid cyclopentane and cyclohexane amino acid analogues were applied by iontophoresis and their relative efficacies were compared with those of the naturally occurring amino acids. 2 GABA was the most effective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Interestingly, Segal et al (1975) found the cyclohexane analogues to be weakly active on hippocampal neurones. Furthermore, these compounds had little effect on root potentials which are thought to involve the release of neutral amino acids (Barker & Nicoll, 1972;Davidoff, 1972;Barker et al, 1975a,b) suggesting that they neither compete for neutral amino acid receptors nor uptake sites.…”
Section: Effects Of Antagonists On Primary Afferent Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Segal et al (1975) found the cyclohexane analogues to be weakly active on hippocampal neurones. Furthermore, these compounds had little effect on root potentials which are thought to involve the release of neutral amino acids (Barker & Nicoll, 1972;Davidoff, 1972;Barker et al, 1975a,b) suggesting that they neither compete for neutral amino acid receptors nor uptake sites.…”
Section: Effects Of Antagonists On Primary Afferent Responsesmentioning
confidence: 99%
“…especially aminocyclopentane carboxylic acids in such a study have been discussed (Segal et al, 1975). It should be kept in mind that the dual action of many of the compounds may have introduced small errors in relative potency, but this problem was minimized by appropriate adjustment of amino acid concentrations.…”
Section: Effects Of Antagonists On Primary Afferent Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…CHCl 3 (200 ml) and water (100 ml) were added to the residue, and the whole was stirred for a few minutes, after which the insoluble material was filtered out using Hyflo Super-Cel 4 aqueous solution (142 ml) were mixed and then vigorously stirred at room temperature for 2 h. The AcOEt layer was separated, and the aqueous layer was extracted with AcOEt (25 mlϫ3). Isopropyl alcohol (1 ml) was added to the combined AcOEt layers, and the solution was left to stand for 1 h. The precipitated RuO 2 was filtered off, and the solution was dried over anhydrous Na 2 12 mmol) in AcOEt (24 ml), RuO 2 · xH 2 O (71 mg), and a 10% NaIO 4 aqueous solution (71 ml) were mixed and then vigorously stirred at room temperature for 3.5 h. The AcOEt layer was separated, and the aqueous layer was extracted with AcOEt (13 mlϫ3). Isopropyl alcohol (0.5 ml) was added to the combined AcOEt layers, and the solution was left to stand for 1 h. The precipitated RuO 2 was filtered off, and the solution was dried over anhydrous Na 2 SO 4 , then concentrated under reduced pressure.…”
Section: Trimethyl (1r*4s*5s*6s*)-2-azabicyclo[222]octane-256-mentioning
confidence: 99%
“…One of the title compounds, (1S,2R)-2-(benzamido)cyclohexanecarboxylic acid, BACO (I), was used as such a chiral resolving agent, 1 but it was originally synthesized in stereochemical studies, 2 and its ciscyclicamino acid is used as an intermediate for an analog of GABA. 3,4 It was considered that (I) and its reduction product, (1S,2R)-2-(benzylamino)cyclohexylmethanol, BACH (II), 5 recognized the amine/amino-alcohol and carboxy groups in diastereomer salts, respectively, but the structures have not been cleared. In this study, the crystal structures of (I) and (II) were determined and correlated with their chemical properties.…”
mentioning
confidence: 99%